2017
DOI: 10.1007/s10569-016-9749-1
|View full text |Cite
|
Sign up to set email alerts
|

On the co-orbital motion in the planar restricted three-body problem: the quasi-satellite motion revisited

Abstract: International audienceIn the framework of the planar and circular restricted three-body problem, we consider an asteroid that orbits the Sun in quasi-satellite motion with a planet. A quasi-satellite trajectory is a heliocentric orbit in co-orbital resonance with the planet, characterized by a non zero eccentricity and a resonant angle that librates around zero. Likewise, in the rotating frame with the planet it describes the same trajectory as the one of a retrograde satellite even though the planet acts as a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 37 publications
4
45
0
Order By: Relevance
“…The maximum amplitude of libration, θ max , which corresponds to the orbit of the last invariant tori of the island region, increases as the orbits become more distant from the Planet. This has been shown also by Pousse et al (2017) with the use of an average model. However, due to the absence of chaos in the averaged model, the maximum amplitude of libration is overestimated.…”
Section: The Planar Circular Restricted Model (Pc-rtbp)supporting
confidence: 53%
See 1 more Smart Citation
“…The maximum amplitude of libration, θ max , which corresponds to the orbit of the last invariant tori of the island region, increases as the orbits become more distant from the Planet. This has been shown also by Pousse et al (2017) with the use of an average model. However, due to the absence of chaos in the averaged model, the maximum amplitude of libration is overestimated.…”
Section: The Planar Circular Restricted Model (Pc-rtbp)supporting
confidence: 53%
“…In the last twenty years, much attention has been given to QS asteroid motion. Evidence for the existence of stable QS-type motion around giant planets of our Solar system has been found after having considered analytical or semi-analytical perturbative methods (Mikkola and Innanen, 1997;Namouni, 1999;Nesvorný et al, 2002;Mikkola et al, 2006;Sidorenko et al, 2014;Pousse et al, 2017) or numerical integrations (Wiegert et al, 2000;Christou, 2000a,b). A lot of studies have also focused on particular observed asteroids and Centaurs e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, if we consider the inclined and/or eccentric cases, the phase space is significantly more complex. New co-orbital configurations appear, such as quasi-satellites (Namouni 1999;Mikkola et al 2006;Sidorenko et al 2014;Pousse et al 2017) in the eccentric case and retrograde co-orbitals (Morais and Namouni 2013) in the inclined one. For no-null eccentricities and/or inclination, secular dynamics kicks in, increasing the number of dimension to consider in order to correctly describe the dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Although the first quasi-satellite (of Jupiter) may have been identified (and lost) in 1973 (Chebotarev 1974), 10 the first bona fide quasi-satellite (of Venus in this case), 2002 VE 68 , was documented by Mikkola et al (2004). A modern theory of quasi-satellites has been developed in the papers by Mikkola et al (2006), Sidorenko et al (2014) and Pousse, Robutel & Vienne (2017). A recent review of confirmed quasi-satellites has been presented by de la Fuente Marcos & de la Fuente Marcos (2016e).…”
Section: The Evolutionmentioning
confidence: 99%